2020
DOI: 10.1093/mnras/staa170
|View full text |Cite
|
Sign up to set email alerts
|

Improved constraints from ultra-faint dwarf galaxies on primordial black holes as dark matter

Abstract: Soon after the recent first ever detection of gravitational waves from merging black holes it has been suggested that their origin is primordial. Appealingly, a sufficient number of primordial black holes (PBHs) could also partially or entirely constitute the dark matter (DM) in the Universe. However, recent studies on PBHs in ultrafaint dwarf galaxies (UFDGs) suggest that they would dynamically heat up the stellar component due to two-body relaxation processes. From the comparison with the observed stellar ve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 79 publications
0
33
0
Order By: Relevance
“…Other constraints of various strengths do exist in this mass range, from lack of mass segregation in Segue 1 (Koushiappas & Loeb 2017), the distribution of widebinary separations (Monroy-Rodríguez & Allen 2014), and lack of an imprint on the cosmic microwave background from accreting primordial black holes (Ali-Haïmoud & Kamionkowski 2017). Another constraint (Stegmann et al 2020), comparing the observed half-light radii of a large sample of UFDs to simulations, also rules out this mass range for dark matter consisting completely of primordial black holes, even when considering extended mass distributions, but the methodology is unable to provide answers for lower abundances. As each of these astrophysical constraints involves assumptions, corroboration from different sources is still valuable, especially considering this mass range is the last window for dark matter purely consisting A107, page 13 of 16 of MACHOs that is not robustly closed by more fundamental physics.…”
Section: Discussionmentioning
confidence: 99%
“…Other constraints of various strengths do exist in this mass range, from lack of mass segregation in Segue 1 (Koushiappas & Loeb 2017), the distribution of widebinary separations (Monroy-Rodríguez & Allen 2014), and lack of an imprint on the cosmic microwave background from accreting primordial black holes (Ali-Haïmoud & Kamionkowski 2017). Another constraint (Stegmann et al 2020), comparing the observed half-light radii of a large sample of UFDs to simulations, also rules out this mass range for dark matter consisting completely of primordial black holes, even when considering extended mass distributions, but the methodology is unable to provide answers for lower abundances. As each of these astrophysical constraints involves assumptions, corroboration from different sources is still valuable, especially considering this mass range is the last window for dark matter purely consisting A107, page 13 of 16 of MACHOs that is not robustly closed by more fundamental physics.…”
Section: Discussionmentioning
confidence: 99%
“…PBHs, formed from SM plasma that collapsed due to its own gravity in the very early Universe, are a possible solution to the DM puzzle [7][8][9][10][11][12][13]. The fraction f PBH of DM in the form of PBHs is constrained to be below unity for PBH masses M PBH ≳ 10 23 g (≈5 × 10 −11 M ⊙ ) via various observations, such as gravitational lensing [14][15][16][17][18][19][20][21][22][23][24], stellar dynamics [25][26][27][28][29][30][31], gravitational waves [32][33][34][35][36][37][38][39][40][41], and the cosmic microwave background (CMB) [42][43][44][45]. The situation is different for lower-mass PBHs, as their gravitational signatures are not strong enough to cause a measurable effect in existing data.…”
Section: Introductionmentioning
confidence: 99%
“…In order to build a realistic model for the star-forming clumps in which IMBHs may reside, we rely on the numerical work of Tamburello et al (2015), where the properties of massive star-forming clumps in isolated galaxies were studied in detail. They performed a large suite of galaxy simulations, to assess the dependence of gas fragmentation properties in a galaxy on sub-grid physics, galaxy mass, structural parameters, and resolution, using the smoothed particle hydrodynamic code gasoline2 (Wadsley et al 2017), an updated version of gasoline (Stadel 2001;Wadsley et al 2004). In this paper, we specifically analyse the clumps forming in their run 27 (see tables 1 and 2 of Tamburello et al 2015), in which they simulated a dark matter halo with an embedded stellar and gaseous disc, with a virial and a baryonic mass of 2.5 × 10 12 and 7.8 × 10 10 M , respectively, a gas fraction of 50 per cent, and a virial concentration of 6.…”
Section: Initial Conditionsmentioning
confidence: 99%
“…Using skid (Stadel 2001), a group finder for N -body simulations, we extracted the mass and half-mass radius of the largest clumps formed in the simulation, finding a typical stellar clump mass…”
Section: Initial Conditionsmentioning
confidence: 99%
See 1 more Smart Citation